TÜRK EDEBİYATINDA NA‘TÎ MAHLASINI KULLANAN ŞAİRLER - Ahmet Yılmaz (İstem, 2003)
It is an important tradition to compose na’t in the Turkish Literature. Naturally it should have been used pseudonym of Na’ti very often. However, in this study, it has been seen that only five persons used this pseudonym in the Turkish Literature